Consumer-To-Consumer Online Market for Used Goods : A Case Study of OLX in India - Rashmi; Nijhawan, Garima (Indian Journal of Marketing, 2016)
Online sale and purchase of second-hand products is on the rise in India. OLX is a free-to-use website for consumer-to-consumer (C2C) online auction of used goods. This study uncovered the needs and expectations of current and potential users of virtual marketplaces of used products. Consumers were studied separately for their perspectives as sellers and as buyers. Existing service performance of OLX was studied and potential hurdles in creating a free online market for second-hand goods was revealed. In-depth interviews, focus group discussions, content analysis, and question-based survey were used for this research. In addition, the paper also discussed the implications of findings for marketers.